(untitled) (REMUNOM, 2025)
We are experiencing a growing demand for qualified labor to work in the automotive maintenance and repair segment, and dealerships are increasingly facing higher costs for maintaining their operations, which will directly influence the resources made available for training specialized labor. The work that will be developed aims to present to employers and recruiters how important the performance of HR (Human Resources) is for the success of an organization. During this work, we will be raising employees’ expectations regarding their workplace and the tools made available for the development of their work activities, and we will also be illustrating the costs of recruiting, training and retaining employees. In this way, we will discuss methods for identifying weaknesses and strengths in organizations in order to list points for improvement to ensure that investments in training of technical staff are not in vain, but that they can deal very professionally when one of the employees is harassed by the competing market and that we have the strength to retain our greatest asset of the company, which is undoubtedly our employees.